Job Satisfaction and Self-Selection into the Public or Private Sector: Evidence from a Natural Experiment - Natalia Danzer (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2013)
Are public sector jobs better than private sector jobs? To answer this question, this paper investigates observed differences in job satisfaction between public- and private-sector workers and disentangles the effect of worker sorting from the one caused by sectorspecific job characteristics. A natural experiment —the massive privatization process inpost-Soviet countries—allows correcting potential self-selection bias. Industry-specificprivatization probabilities are assigned to workers based on unique individual-level surveyinformation regarding pre-determined Soviet jobs during the 1980s. The results reveal acausal public-sector satisfaction premium and a negative selection of individuals intothe public sector. Part of the public-private satisfaction gap can be explained by thedifferent availability of fringe benefits in the two sectors.
Keywords: J28; J45; J31; J32; 330; Public sector; job satisfaction; self-selection; quasi-experiment; privatization; fringe benefits.